Wall construction / Muhamad Ikram Mohd Rozy - Mohd Rozy, Muhamad Ikram (Universiti Teknologi MARA, Perak, 2021)
Wall could be a structural feature that divides or encloses an area and, in building construction, forms the space or building's perimeter. Traditional masonry construction required exterior walls to support the burden of floors and roofs, but modern steel and reinforced concrete frames, moreover as heavy timber, and other skeletal structures, only require exterior walls for shelter and sometimes do away with them entirely on the bottom floor to permit easier access. This report will discuss about wall construction. This report was conducted for the development of Single Storey House at GM 3652, Lot 14898, Mukim Kadok Dalam, Kota Bharu, Kelantan. the target of this report is to research the development of wall and therefore the way how it disbursed. it'll specialize in the entire process of wall construction. It also investigates the equipment and machinery within the methods of wall construction and to see the time that are used for the development. This report also will look to at the matter and the solution in wall construction that might fulfill the factors of wall.